IMPLEMENTASI MODEL GOAL FREE EVALUATION PADA PROGRAM LITERASI BACA TULIS DI SD NEGERI KENEP 01 SUKOHARJO - Nourma Ayu Sulistiyowati; Yusuf Nurrahman; Definka Puan Shalika Abdillah; Sumardi Sumardi; Suranto Suranto (Jurnal Manajemen Pendidikan, 2026)
This study aims to evaluate the literacy program at SD Negeri Kenep 01 Sukoharjo using the Goal-Free Evaluation (GFE) model developed by Michael Scriven. Employing a qualitative approach with a program evaluation design, the study focuses on identifying the actual impacts of the program without relying on its predetermined objectives. Data were collected through interviews, observations, and document analysis and were analyzed using an interactive process of data reduction, data presentation, and conclusion drawing. The findings reveal that the literacy program achieved its intended outcomes by improving students’ reading interest, writing skills, and Indonesian language learning achievement. In addition, the evaluation identified several unintended impacts, both positive and negative. Positive outcomes included the development of a stronger literacy culture within the school, the enhancement of students’ positive character traits, and increased parental involvement in supporting literacy activities. Conversely, unintended negative impacts included student boredom and an additional workload for teachers. These findings demonstrate that the Goal-Free Evaluation model provides a more comprehensive understanding of program effectiveness than objective-based approaches and offers valuable insights for strengthening internal evaluation mechanisms, diversifying reading materials, improving teacher capacity, and fostering stronger partnerships between schools and families to ensure the sustainability of literacy programs.